EFFECT OF DIFFERENT SOURCES AND LEVELS OF SILICON APPLICATION ON GROWTH, YIELD ATTRIBUTES AND YIELD OF RICE (Oryza sativa L.) - and D. SRINIVASA CHARY, N.R. SUDHAKARA, T. ANJAIAH, ABDUL AZIZ QURESHI, G.E.CH.VIDYA SAGAR (The Journal of Research, PJTSAU, 2020)
A field experiment was conducted to study the effect of different sources and levels of silicon fertilization on growth, yield and yield attributes of rice during kharif and rabi season of 2018 at College Farm, College of Agriculture, Rajendranagar. Experiment was laid out in randomized block design with fourteen treatments and three replications consisting of four silica sources and three levels of silicon fertilizers along with one RDF(100:40:40 NPK) and one absolute control. Results showed that application of silica through different sources with different levels significantly increased grain and straw yield as well as yield attributing parameters such as plant height, number of panicles hill-1, length of panicle (cm), number of filled grains panicle-1 and 1000 grain weight (g). The application of RDF + FYM + 450 kg silicon per hectare through diatomaceous earth recorded significantly higher grain and straw yieldof 8547 kg ha-1and 10204 kg ha-1 respectively.Higher grain and straw yield under this particular treatment was mainly attributed to higher growth and yield parameters like higher plant height (87.50 cm), number of panicles hill-1 (19.44), length of panicle (23.47 cm), number of grains panicle-1 (269.30), and 1000 grain weight (13.67 g) at harvest.